STUDI PENDAHULUAN BATAS MAKSIMUM KADAR LUMPUR PADA AGREGAT BETON GEOPOLIMER - Djedjen Achmad; Desi Supriyan (Politeknik Negeri Jakarta, 2019)
ABSTRACTHas been researched the impact of mud in aggregate on geopolymer concrete with studies using the cement concrete as a reference. In this study both of concrete are mixed with a variation of mud of 0%, 0.75%, 3% and 5.75% of the combined aggregate weight. Compressive strength of cement concrete is designed with a target of 300 kg / cm2 and geopolymer concrete is made with water binder ratio (w/b) 0.25, Molarity 12 M, the ratio of sodium silicate and sodium hydroxide 1.5. At the age of 3, 7, 14 and 28 day tested of compressive strength, while the spliting test, flexural tensile strength, and modulus of elasticity are tested at 28 days. From the test results, the higher mud content in aggregate , the mechanical properties of the concrete are decreased. Based on testing of compressive strength in cement concrete at 28 days, with a 3% mud content (the content of the reference mud) turns of compressive strength decreased by 77.356%. Of the percentage reduction on the compressive strength of the cement concrete, can be compared to the mud content in geopolymer concrete at 2.04%. Thus the maximum mud on geopolymer concrete aggregate is, for coarse aggregate of 0.68% and a maximum mud content for fine aggregate was 3.4%.Key words : Mud, aggregate, concrete, cement, geopolimer, strengthABSTRAKTelah diteliti dampak kadar lumpur pada agregat untuk beton geopolimer dengan penelitian menggunakan benda uji beton semen sebagai acuan dan beton geopolimer. Dalam penelitian ini ke dua beton tersebut dicampur dengan lumpur gabungan agregat kasar dan agregat halus dengan variasi 0 %, 0.75 %, 3 % dan 5,75 % dari berat agregat gabungan. Beton semen dirancang dengan target kuat tekan 300 kg/cm2 dan beton geopolimer dibuat dengan campuran water binder ratio (w/b) 0.25, Molaritas 12 M, perbandingan sodium silikat dan sodium hidroksida 1.5. Pada umur 3, 7, 14 dan 28 hari dilakukan uji kuat tekan, sedangkan uji kuat tarik belah, uji kuat tarik lentur, dan modulus elastisitas dilakukan pada umur 28 hari. Dari hasil uji terlihat bahwa semakin tinggi kadar lumpur pada agregat, karakteristik mekanis kedua beton tersebut mengalami penurunan. Berdasarkan pengujian kuat tekan pada beton semen umur 28 hari, dengan kadar lumpur 3 % (kadar lumpur referensi) ternyata beton semen mengalami penurunan kuat tekan sebesar 77.356 %. Dari persentase penurunan kuat tekan beton semen tersebut, diplot pada grafik kuat tekan beton geopolimer maka persentase kadar lumpur gabungan yang mengalami penurunan 77.356 % adalah 2.04 %. Dengan demikian kadar lumpur maksimum pada agregat beton geopolimer adalah, untuk agregat kasar sebesar 0.68 % dan kadar lumpur maksimum untuk agregat halus adalah 3.4 %.Kata kunci : Lumpur, agregat, beton, semen, geopolimer, kekuatan